Development of Youthful-Looking Makeup Foundation by Controlling Transmitted Light - Fukuda, Keiichi; Iwamoto, Hiroshi; Igarashi, Takanori; Nakao, Keisuke; Nojiri, Naoki; Kashimoto, Akio; Oosaki, Kazutomo; Uematsu, Takafumi; Minami, Koji; Osada, Miyuki; Uehara, Koichi (Journal of Society of Cosmetic Chemists of Japan, 2010)
Based on the factor analysis of facial appearance using facial texture images, it was found that evenness of skin produced a youthful appearance. We developed a new composite powder which has the optical property to provide ‘youthful-looking’ skin. Facial images of 161 women volunteers with make-up were prepared, and the appearance of skin and face were evaluated by 15 subjects. The results of correlation analysis showed that ‘evenness of skin texture’ and ‘color evenness’ caused a ‘youthful impression’. In order to obtain the evenness of skin, we attempted to develop a new powder that has an ideal optical property of transmitted light. Titanium oxidecontaining silica/color pigment composite powder prepared by the super critical solution method had effective light transmission, diffusion and chroma saturation. We achieved the production of a youthful appearance by application of the composite powder as an ingredient of a foundation.